Inflammatory bowel disease: tri-directional relationship between microbiota, immune system and intestinal epithelium. (4th March 2021) - Ahlawat, Shruti; Kumar, Pramod; Mohan, Hari; Goyal, Sandeep; Sharma, Krishna Kant
Abstract: Human gut microbiota contributes to host nutrition and metabolism, sustains intestinal cell proliferation and differentiation, and modulates host immune system. The alterations in their composition lead to severe gut disorders, including inflammatory bowel disease (IBD) or inflammatory bowel syndrome (IBS). IBD including ulcerative colitis (UC) and Crohn's disease (CD) are gamut of chronic inflammatory disorders of gut, mediated by complex interrelations among genetic, environmental, and internal factors. IBD has debateable aetiology, however in recent years, exploring the central role of a tri-directional relationship between gut microbiota, mucosal immune system, and intestinal epithelium in pathogenesis is getting the most attention. Increasing incidences and early onset explains the exponential rise in IBD burden on health-care systems. Industrialization, hypersensitivity to allergens, lifestyle, hygiene hypothesis, loss of intestinal worms, and gut microbial composition, explains this shifted rise. Hitherto, the interventions modulating gut microbiota composition, microfluidics-based in vitro gastrointestinal models, non-allergic functional foods, nutraceuticals, and faecal microbiota transplantation (FMT) from healthy donors are some of the futuristic approaches for the disease management.